2022
DOI: 10.1186/s12880-022-00745-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the value of enhanced CT combined with texture analysis in the differential diagnosis of pulmonary sclerosing pneumocytoma and atypical peripheral lung cancer: a feasibility study

Abstract: Background As a rare benign lung tumour, pulmonary sclerosing pneumocytoma (PSP) is often misdiagnosed as atypical peripheral lung cancer (APLC) on routine imaging examinations. This study explored the value of enhanced CT combined with texture analysis to differentiate between PSP and APLC. Methods Forty-eight patients with PSP and fifty patients with APLC were retrospectively enrolled. The CT image features of the two groups of lesions were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Similar to our results, recent studies have also demonstrated the efficacy of radiomics models in dis-tinguishing PSP from other malignant lung tumors. For instance, Luo et al 20 investigated the value of CECT combined with texture analysis in differentiating PSP from atypical peripheral lung cancer, and achieved an AUC value of 0.72 for their CT texture-based model. Similarly, Xiao et al 21 assessed the diagnostic value of radiomics-based texture analysis in differentiating PSP from solid malignant pulmonary nodules on singleand three-phase CT images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our results, recent studies have also demonstrated the efficacy of radiomics models in dis-tinguishing PSP from other malignant lung tumors. For instance, Luo et al 20 investigated the value of CECT combined with texture analysis in differentiating PSP from atypical peripheral lung cancer, and achieved an AUC value of 0.72 for their CT texture-based model. Similarly, Xiao et al 21 assessed the diagnostic value of radiomics-based texture analysis in differentiating PSP from solid malignant pulmonary nodules on singleand three-phase CT images.…”
Section: Discussionmentioning
confidence: 99%
“…18 Recently, several studies have highlighted the clinical value of radiomics in discriminating benign from malignant pulmonary lesions. [19][20][21][22] To the best of our knowledge, there were only two studies published to investigate the diagnostic value of radiomics in differentiating PSP from pulmonary malignancy. One focused on PSP versus solid malignant pulmonary nodules,the other focused on PSP versus atypical peripheral lung cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, invasive growth is distributed near the pleura or hilum, or there are malignant signs such as burrs and pleural depression, which are easily misdiagnosed as lung cancer and require careful clinical decision-making. In one report, enhanced CT combined with texture analysis was used to locate calcification, and arterial phase CT values could assist in differentiating PSP from peripheral lung cancer ( 17 ). Depending on the different tissue structures of the lesion, different degrees of enhancement may occur in the early stage after enhanced scanning ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…CECT images often reflect the blood supply to the lesion, and enhancement attenuation helped distinguish between benign and malignant pulmonary nodules ( 16 , 17 ). In terms of radiomics, CECT combined with texture analysis had a good diagnostic value for distinguishing pulmonary sclerosing pneumocytoma and atypical peripheral lung cancer, with a sensitivity and specificity of 0.82 and 0.87, respectively ( 18 ). The study of Liu et al ( 19 ) showed that texture analysis of CECT could be used to evaluate the pathological grade of lung adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%